Peran Pengabdian Mahasiswa dalam Meningkatkan Literasi Al-Qur'an di Masyarakat : Studi Kasus di Binjai, Kabupaten Langkat - Siti Jubaidah; Riski Wahyudi; Sajidah Tambunan; Nur Saniyah Siregar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Community service is an integral part of higher education which aims to provide a positive impact on the community. The service program implemented in Binjai, Langkat Regency, aims to increase Al-Qur'an literacy among the community through the method of reciting and reciting the Al-Qur'an. This activity involves students as facilitators in guiding the reading of the Al-Qur'an, teaching Iqro, and coordinating learning with the target of completing 30 juz in nine days. The main methods applied are talaqqi and classical, which have proven effective in accelerating understanding and fluency in reading the Al-Qur'an. The results of this program show a significant increase in the ability to read the Al-Qur'an, both in terms of fluency and understanding of recitation. Apart from that, this activity also has an impact on the social aspect by strengthening relationships between community members and fostering religious enthusiasm. It is hoped that this program can become a model for increasing religious literacy in society and will continue to be developed with more sustainable innovation.